2015
DOI: 10.1016/j.proeng.2015.07.356
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Assessment of Sustainable Neighborhood Projects through NEST, a Decision Support Tool for Early Stage Urban Planning

Abstract: Urban planners are facing a growing demand for high performance projects in terms of control and reduction of environmental impacts. However, the complex and multi-dimensional concept of sustainable urban development often loses its core substance when confronted to practice realities of urban projects because of a lack of adapted decision support tools. The question arises as to how the effective consideration of the environment and the limitation of the project impacts can be taken into account as soon as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 4 publications
0
14
0
4
Order By: Relevance
“…Olivier-Sol a et al [15] found that it is highly likely that the environmental and energy issues we are currently dealing with at the building level will soon be transferred to the urban scale. Lotteau et al [16] explained that the neighborhood life cycle analysis is complex, multifunctional, and changing and that its life is long. These previous studies raise many new issues regarding how to apply the LCA method at the neighborhood scale, especially regarding the definition of the functional unit or the consideration of temporal aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Olivier-Sol a et al [15] found that it is highly likely that the environmental and energy issues we are currently dealing with at the building level will soon be transferred to the urban scale. Lotteau et al [16] explained that the neighborhood life cycle analysis is complex, multifunctional, and changing and that its life is long. These previous studies raise many new issues regarding how to apply the LCA method at the neighborhood scale, especially regarding the definition of the functional unit or the consideration of temporal aspects.…”
Section: Introductionmentioning
confidence: 99%
“…"Photochemical ozone production" is reduced by more than 50% over the entire life cycle of the neighborhood. In fact, the combustion of fuels is the main source of nitrogen oxide production, which transforms into ozone under the effect of sunlight [64]. In our urban site scenario, 54% of photochemical ozone production in the use phase is avoided, by reducing the use of automobiles.…”
Section: Mobility Flow Impact Assessmentmentioning
confidence: 99%
“…Comparing the scores of the environmental indicators only for the heating items during the use phase, as also for both orientations, we notice an 11% increase in the greenhouse effect, as well as a cumulative energy demand and depletion of abiotic resources for the 90 • orientation. Thus, the orientation has an impact on heating consumption and on environmental indicators relating only to these [62][63][64][65]. However, at the neighborhood level, this orientation has little impact on the overall results of the LCA.…”
Section: Orientation Impact Assessmentmentioning
confidence: 99%
“…In total, more than 250 construction LCA documents were referenced in 2015 [4]. Several review articles have been published in the field of LCA in buildings between 2009 and 2014, and at least 10 review articles in 2015-2016 [6,11,14,[27][28][29][30][31][32]. From top to bottom, there have been additional critical reviews articles on the construction of LCA [4,33,34].…”
Section: A Brief Litterature Reviewmentioning
confidence: 99%